2020
DOI: 10.1038/s41388-020-1299-z
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ and EGF signaling orchestrates the AP-1- and p63 transcriptional regulation of breast cancer invasiveness

Abstract: Activator protein (AP)-1 transcription factors are essential elements of the pro-oncogenic functions of transforming growth factor-β (TGFβ)-SMAD signaling. Here we show that in multiple HER2+ and/or EGFR+ breast cancer cell lines these AP-1-dependent tumorigenic properties of TGFβ critically rely on epidermal growth factor receptor (EGFR) activation and expression of the ΔN isoform of transcriptional regulator p63. EGFR and ΔNp63 enabled and/or potentiated the activation of a subset of TGFβ-inducible invasion/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 56 publications
5
57
0
Order By: Relevance
“…The elevation of FOS-like antigen 1 expression is positively correlated with the progression of perihilar cholangiocarcinoma [ 25 ]. More importantly, a prior research illustrated that FOS was involved in gene expression regulated by TGF-β [ 26 ]. Furthermore, the tumor-promoting effects of TGF-β signaling pathway have been reported in cholangiocarcinoma [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of FOS-like antigen 1 expression is positively correlated with the progression of perihilar cholangiocarcinoma [ 25 ]. More importantly, a prior research illustrated that FOS was involved in gene expression regulated by TGF-β [ 26 ]. Furthermore, the tumor-promoting effects of TGF-β signaling pathway have been reported in cholangiocarcinoma [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human colon cancer HCT-116 and CACO-2 cells were grown in McCoy′s 5a medium (Sigma-Aldrich Sweden AB, Stockholm, Sweden) and in Minimum Essential Medium Eagle (Sigma-Aldrich Sweden AB, Stockholm, Sweden), respectively (both cell lines were kindly provided by Dr I. Ferby, Uppsala University, being purchased from ATCC). Ras-transformed premalignant MCF10AneoT (MII) cells [ 59 ] were cultured in DMEM/F12 (Gibco, Life Technologies Europe BV, Stockholm, Sweden). Cells were maintained at 5% CO 2 in a humidified atmosphere at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we identified yet another CSC marker; COL17A1, a novel TP53 target [ 42 ] and a frequently mutating gene in breast cancer ( Table S3 ), is known to be involved in the regulation of both cell migration and invasion [ 42 , 43 ]. Moreover, additional markers identified include EGFR, AP-1, p63, and TGF-β, as their pro-oncogenic functions regulate breast cancer invasiveness, and therefore, these can be exploited as therapeutic targets in breast cancer [ 44 ]. The p53 family member p63 is a transcriptional regulator of epithelial development and differentiation; moreover, p63 is also involved in the transcriptional regulation of EGFR genes [ 44 ], frequently mutating genes in breast cancer ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional markers identified include EGFR, AP-1, p63, and TGF-β, as their pro-oncogenic functions regulate breast cancer invasiveness, and therefore, these can be exploited as therapeutic targets in breast cancer [ 44 ]. The p53 family member p63 is a transcriptional regulator of epithelial development and differentiation; moreover, p63 is also involved in the transcriptional regulation of EGFR genes [ 44 ], frequently mutating genes in breast cancer ( Table S3 ). In addition, in this study, we identified TP63, an EMT gene, as a member of a 13-gene signature for overall survival.…”
Section: Discussionmentioning
confidence: 99%